2011
DOI: 10.1038/srep00144
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing apoptosis in TRAIL-resistant cancer cells using fundamental response rules

Abstract: The tumor necrosis factor related apoptosis-inducing ligand (TRAIL) induces apoptosis in malignant cells, while leaving other cells mostly unharmed. However, several carcinomas remain resistant to TRAIL. To investigate the resistance mechanisms in TRAIL-stimulated human fibrosarcoma (HT1080) cells, we developed a computational model to analyze the temporal activation profiles of cell survival (IκB, JNK, p38) and apoptotic (caspase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 54 publications
3
31
0
Order By: Relevance
“…To tackle this challenge the cancer field would benefit from detailed characterization of the genetic and epigenetic makeup of patient-derived tumors to identify defects in cell proliferation and death pathways[79]. Computational modeling could prove invaluable to help collate and interpret huge datasets, finding novel targets that might enhance apoptosis in TRAIL-resistant populations[80]. To complement this approach, preclinical studies should focus on using primary patient-derived cell lines as opposed to established cancer cell lines.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…To tackle this challenge the cancer field would benefit from detailed characterization of the genetic and epigenetic makeup of patient-derived tumors to identify defects in cell proliferation and death pathways[79]. Computational modeling could prove invaluable to help collate and interpret huge datasets, finding novel targets that might enhance apoptosis in TRAIL-resistant populations[80]. To complement this approach, preclinical studies should focus on using primary patient-derived cell lines as opposed to established cancer cell lines.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…3C suggest that MT-6 activates cleavage of caspase-8 and -9, representing extrinsic (death receptor) and intrinsic (mitochondria) pathways of apoptosis, respectively. Previous studies have indicated that TRAIL-induced cell death signaling is related to both extrinsic and intrinsic apoptotic pathways, and may be a promising therapeutic pathway for targeting by single agents or combined treatment with conventional chemotherapies2930. To delineate the mechanism of MT-6–induced cell death, we further examined the levels of death receptors for pro-apoptotic signaling, such as transmembrane death receptors belonging to the tumor necrosis factor receptor (TNFR) superfamily.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies showed that the absence of FADD leads to partial TRAIL-resistance and concluded that FADD is necessary for TRAIL-induced apoptosis by the death receptors DR4 and DR5 (74,75). Other groups showed that the induction of apoptosis by TRAIL is independent of FADD in different cell lines (73,76,77). Additionally, FADD was described as a negative regulator of the transcription factor NF-κB (nuclear factor κ-light chain-enhancer of activated B-cells), which promotes cell survival and tumour invasiveness of fibrosarcoma cells (78,79).…”
Section: Discussionmentioning
confidence: 99%